Differentiation Of Leukocytes Cat Fish (Mystus Nemurus) Fed Solutions Containing Curcuma (Curcuma Xanthorrhiza) - Juandi Riki Umbara Siagian; Iesje Lukistyowati; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The effect of containing curcuma (Curcuma xanthorrhiza Roxb) on diferentiation of leukocytes of Cat Fish (Mytus nemurus). The aim of the study is to find of diferentiation of leukocyte of Cat Fish (Mytus nemurus). The study was conducted from March to April 2014 in the Experimental Pond and Laboratory of Parasitic Diseases of Fish and Fisheries and Marine Sciences Faculty of the Riau University. The method used was experimental method using RAL with one factor with 4 level treatments and three repliations. the result indicate that the best differentiation of leukocytes in the P3 treatment is total leukocytes (96.538 cell/mm3), diferentiation of leukocytes (lymphocytes: 96,67%, monocytes: 1,67%, and neutrophils: 1,67%) and the best treament of survival rate is P2 and P3 with survival rate is 100%.Keywords: Differentiation, Leukocytes, Cat Fish, and Curcuma Solution